PELATIHAN PENYUSUNAN MODUL AJAR BERBANTUAN SOFTWARE MATEMATIKA UNTUK PENGUATAN PROGRAM SMK PUSAT KEUNGGULAN - Nur Prabawati, Mega; Mulyani, Eva; Yulianto, Eko; Zulfikar Mansyur, Muhammad (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
The use of information technology, especially computer-based applications, is able to facilitate the learning process. In the application of computer-based learning, it is not only seen from the ability of teachers to use and utilize computers in learning, but teachers are also required to be more innovative and follow developments in information technology in the learning process. Among them, the use of applications or software that supports the learning process. One of the mathematical software that can be used in the learning process is GeoGebra software. In this pendemi period the use of GeoGebra software really helped teachers in compiling material and explaining material to students. Through this Community Service activity, the cominity team helps partners by providing training in using GeoGebra software. This training aims to make SMK teachers more skilled in utilizing media in learning. This community activity was carried out in a demonstration, where the community team first provided material about GeoGebra software, and continued by providing training using GeoGebra software to the training participants. By doing so, it is hoped that these teachers will be able to utilize GeoGebra software in the learning process.